Development Of Professional Competence In Higher Education Is The Basis Of Training Specialist - Ikrom Kodirov (Euro Asian Journal Publishing, 2024)
The article was discussed the role of competence in pedagogical education, professional competence, formation of students as competitive specialists based on the creation of a professional educational environment in a higher educational institution, methods of developing the professional competence of students of higher educational institutions.
Keywords: Competence; pedagogical education; ability